Expression pattern and prognostic significance of CDKs in breast cancer: An integrated bioinformatic study - Mehraj, Umar; Sofi, Shazia; Alshehri, Bader; Mir, Manzoor A (Cancer biomarkers : section A of Disease markers, 2022)
Globally, breast cancer (BC) has become one of the most prevalent malignancies and the leading cause of tumor-related deaths among women. Dysregulation of the cell cycle is a well-known hallmark of cancer development and metastasis. CDKs are essential components of the cell-cycle regulatory system with aberrant expression in a variety of cancers, including BC. In the development of targeted cancer treatment, reestablishing the regulation of the cell cycle by modulation of CDKs has emerged as a promising approach. Herein, we used a bioinformatic approach to assess the expression pattern, prognostic and diagnostic importance, and clinical relevance of CDKs in BC. Additionally, we conducted a functional enrichment analysis of deregulated CDKs using the STRING and KEGG databases to delineate the role of CDKs in breast tumorigenesis. Gene expression analysis revealed substantial deregulation of CDKs in BC, with CDK1, CDK11A, and CDK18 showing a fold change of >± 1.5. Also, metastatic tumors showed high expression of CDK1 in the single cell RNA sequencing analysis of primary and metastatic breast tumors. Additionally, it was found that dysregulated CDK expression affects overall survival (OS) and relapse-free survival (RFS) of BC patients. The study's multimodal analytical methodologies imply that modulating CDKs for BC treatment is a promising approach.